The Influence of Christian Religious Education Courses On Integrity and Student Morality Of The Faculty of MIPA, HKBP Nommensen University, Pematangsiantar - Esther Romaartana Sitorus; Reagan Surbakti Saragih; Tri Susi Talenta Sinaga (CV Putra Publisher, 2026)
The purpose of this study was to analyze the effect of Christian Religious Education (PAK) courses on the integrity and morality of FMIPA students in Semester I of the 2024/2025 academic year at HKBP Nommensen Pematangsiantar University. The research method used was quantitative with a survey approach with a research sample of 50 students selected purposively. The research instrument was a Likert scale questionnaire containing indicators of integrity (academic honesty, responsibility, consistency) and morality (ethical attitudes, social concern, adherence to norms). The data were analyzed using simple linear regression and Pearson correlation tests. The results showed that PAK courses had a positive and significant effect on improving student integrity and morality. The coefficient of determination (R²) value of 0.62 indicated that 62% of the variation in student integrity and morality was influenced by PAK courses, while 38% was influenced by other factors outside this study. Thus, it can be concluded that Christian religious education plays a crucial role as a means of transforming religious and ethical values in an academic context, as well as serving as a foundation for developing student character with integrity, morality, and social responsibility